Neurological Outcome Following Newborn Encephalopathy With and Without Perinatal Infection: A Systematic Review - Mads Andersen; Mads Andersen; Mette Vestergård Pedersen; Ted Carl Kejlberg Andelius; Kasper Jacobsen Kyng; Kasper Jacobsen Kyng; Tine Brink Henriksen; Tine Brink Henriksen (Frontiers in Pediatrics, 2021)
Background: Studies have suggested that neurological outcome may differ in newborns with encephalopathy with and without perinatal infection. We aimed to systematically review this association.Methods: We conducted this systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Studies were obtained from four databases including Pubmed, Embase, Web of Science, and The Cochrane Database. Newborns with encephalopathy with and without markers of perinatal infection were compared with regard to neurodevelopmental assessments, neurological disorders, and early biomarkers of brain damage. Risk of bias and quality of evidence were assessed by the Newcastle-Ottawa scale and Grading of Recommendations Assessment, Development and Evaluation (GRADE).Results: We screened 4,284 studies of which eight cohort studies and one case-control study met inclusion criteria. A narrative synthesis was composed due to heterogeneity between studies. Six studies were classified as having low risk of bias, while three studies were classified as having high risk of bias. Across all outcomes, the quality of evidence was very low. The neurological outcome was similar in newborns with encephalopathy with and without markers of perinatal infection.Conclusions: Further studies of higher quality are needed to clarify whether perinatal infection may affect neurological outcome following newborn encephalopathy.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42020185717.